2022
DOI: 10.1002/path.6028
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular characterization of esophageal basaloid squamous cell carcinoma: a subtype with distinct RNA expression pattern and immune characteristics, but no specific genetic mutations

Abstract: Esophageal basaloid squamous cell carcinoma (bSCC) is a subtype of squamous cell carcinoma (SCC) with a different behavior and poor prognosis. Exploring bSCC's molecular characteristics and treatment strategies are of great clinical significance. We performed multi-omics analysis of paired bSCC and common SCC (cSCC) using whole exome sequencing and a NanoString nCounter gene expression panel. Immunohistochemistry was used for verification of candidate biomarkers. Different treatment response was analyzed on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…7 They also reported a worse response of immune-chemotherapy in basaloid squamous cell carcinoma. 7 This poor immune response tendency might be similar in the same subtype of lung cancer, and might be the reason for the rarity of SR in basaloid squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 They also reported a worse response of immune-chemotherapy in basaloid squamous cell carcinoma. 7 This poor immune response tendency might be similar in the same subtype of lung cancer, and might be the reason for the rarity of SR in basaloid squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that basaloid squamous cell carcinoma accounts for 3.9%–5.2% of all lung squamous carcinomas, and typically show rapid clinical progression, rapid growth rate, and a poorer prognosis compared to conventional squamous cell carcinoma of the lung 5,6 . Li et al performed the molecular characteristic comparison of basaloid squamous cell carcinoma and common squamous cell carcinoma of the esophageal, and reported that basaloid squamous cell carcinoma showed downregulation of CCL21 which associated with immune response 7 . They also reported a worse response of immune‐chemotherapy in basaloid squamous cell carcinoma 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation